2021
DOI: 10.1111/jce.14964
|View full text |Cite
|
Sign up to set email alerts
|

His–Purkinje system longitudinal dissociation: From bench to bedside. A case of output‐dependent fascicular capture

Abstract: Introduction: Histological studies reported that the His bundle (HB) is partitioned into narrow cords by collagen running in its long axis, providing the anatomical setting necessary for its longitudinal dissociation. Further confirmations came from the demonstration that direct HB pacing normalizes the QRS axis and duration in subjects with proximal HB lesions causing bundle branch block. However, there is no evidence of the possibility of selective HB partitions pacing destined to the composition of branches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, higher voltages are needed in less optimal positions (non-selective HBP). [ 48 ] Bednarek et al investigated mechanical dyssynchrony using speckle tracking echocardiography in patients during selective and non-selective HBP. [ 49 ] Speckle tracking images showed premature contraction in the basal septal segment only during non-selective HBP, but this was confined to the basal septum and basal inferior segment.…”
Section: What Is Known About Left Ventricular Septal His Bundle and Left Bundle Branch Pacing ?mentioning
confidence: 99%
“…However, higher voltages are needed in less optimal positions (non-selective HBP). [ 48 ] Bednarek et al investigated mechanical dyssynchrony using speckle tracking echocardiography in patients during selective and non-selective HBP. [ 49 ] Speckle tracking images showed premature contraction in the basal septal segment only during non-selective HBP, but this was confined to the basal septum and basal inferior segment.…”
Section: What Is Known About Left Ventricular Septal His Bundle and Left Bundle Branch Pacing ?mentioning
confidence: 99%
“…We believe this phenomenon has been referred to as output‐dependent fascicular capture. Different outputs can selectively activate different portions of conduction system and produced asynchronous conduction in the HPS 9,10 . At the initial threshold testing, pacing output at 2 V/0.5 ms activated the HPS and the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies performed in dogs, however, conclusively demonstrated the presence of functional transverse interconnections within the non‐branching bundle, failing to demonstrate the delivery of the stimulus to specific ventricular areas (Lazzara et al, 1973). The topic, however, is far from settled, as evidence of dissociation has allegedly been found in pathological situations (Marinaccio et al, 2021; Sherif et al, 1974; Zhang, 2014) In this regard, a letter commenting on the publication of James and Sherf (Lev, 1971), emphasized the difficulty in establishing the presence of morphological dissociation when only using evidence depending on two‐dimensional anatomy, this being the methodology of the studies performed at that time. It was argued that three‐dimensional reconstructions would provide the best means of proving or disproving the presence of lateral or transverse interconnections.…”
Section: Introductionmentioning
confidence: 99%